Critical roles of nicotinic acetylcholine receptors in olfactory memory formation and retrieval in crickets - Matsumoto, Yukihisa; Matsumoto, Chihiro Sato; Mizunami, Makoto (Frontiers in Physiology, 2024)
Acetylcholine (ACh) is a major excitatory neurotransmitter in the insect central nervous system, and insect neurons express several types of ACh receptors (AChRs). AChRs are classified into two subgroups, muscarinic AChRs and nicotinic AChRs (nAChRs).nAChRs are also divided into two subgroups by sensitivity to α-bungarotoxin (α-BGT).The cricket Gryllus bimaculatus is one of the useful insects for studying the molecular mechanisms in olfactory learning and memory. However, the roles of nAChRs in olfactory learning and memory of the cricket are still unknown. In the present study, to investigate whether nAChRs are involved in cricket olfactory learning and memory, we tested the effects of two different AChR antagonists on long-term memory (LTM) formation and retrieval in a behavioral assay. The two AChR antagonists that we used are mecamylamine (MEC), an α-BGT-insensitive nAChR antagonist, and methyllycaconitine (MLA), an α-BGT-sensitive nAChR antagonist. In crickets, multiple-trial olfactory conditioning induced 1-day memory (LTM), whereas single-trial olfactory conditioning induced 1-hour memory (mid-term memory, MTM) but not 1-day memory. Crickets injected with MEC 20 min before the retention test at 1 day after the multiple-trial conditioning exhibited no memory retrieval. This indicates that α-BGT-insensitive nAChRs participate in memory retrieval. In addition, crickets injected with MLA before the multiple-trial conditioning exhibited MTM but not LTM, indicating that α-BGTsensitive nAChRs participate in the formation of LTM. Moreover, injection of nicotine (an nAChR agonist) before the single-trial conditioning induced LTM. Finally, the nitric oxide (NO)-cGMP signaling pathway is known to participate in the formation of LTM in crickets, and we conducted co-injection experiments with an agonist or inhibitor of the nAChR and an activator or inhibitor of the NO-cGMP signaling pathway. The results suggest that nAChR works upstream of the NO-cGMP signaling system in the LTM formation process.